C++ standard library quick reference - Weert, Peter van; Gregoire, Marc (The expert's voice in C++, 2016)
This quick reference is a condensed reference guide to the essential data structures, algorithms, and functions provided by the C++ Standard Library. More specifically, this is a compact collection of essential classes and functions, used by C++ programmers on a daily basis. The C++ Standard Library Quick Reference features core classes for strings, I/O streams, and various generic containers, as well as a comprehensive set of algorithms to manipulate them. In recent years, the C++11 and C++14 standards have added even more efficient container classes, a new powerful regular expression library, and a portable multithreading library featuring threads, mutexes, condition variables, and atomic variables. Needless to say, it is hard to know and remember all the possibilities, details, and intricacies of this vast and growing library. This handy reference guide is therefore indispensable to any C++ programmer. It offers a condensed, well-structured summary of all essential aspects of the C++ Standard Library, including all aforementioned functionality. No page-long, repetitive examples or obscure, rarely used features. Instead, everything you need to know and watch out for in practice is outlined in a compact, to-the-point style, interspersed with well-chosen, clarifying examples. The book does not explain the C++ language or syntax, but is accessible to anyone with basic C++ knowledge. Even the most experienced C++ programmer though will learn a thing or two from it and find it a useful memory-aid.